A brief history of Cia Ludens and its productions of Irish plays in Brazil - Domingos Nunez (Ilha do Desterro)
This essay intends to give an account of the activities undertaken by Cia Ludens, a professional Brazilian theatre company, since its foundation in 2003 up to present days. With the sole purpose of translating and producing Irish plays in Brazil, mainly by contemporary dramatists, and establishing possible connections with the Brazilian reality, the company has so far produced four plays and three staged readings, designed to show part of its researching process. Interwoven by the concept of "play", the reflections presented here reveal how some of Huizinga's ideas influenced the company's artistic choices in its various productions.